Pendidikan Karakter Dalam Pembelajaran Pendidikan Jasmani Sekolah Dasar : A Systematic Review - Baharuddin, Syaipul Hari; Satrio, Shandy; Permana, Gilang; Carsiwan, Carsiwan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to analyze the application of character education in educational learning through a systematic literature observation approach. The method used is a systematic literature review by identifying, assessing, and synthesizing various relevant research referring to the 2020 PRISMA guidelines. The research results show that character education in physical education can increase values ​​such as cooperation, discipline, responsibility, and respect in among students. In addition, various learning strategies and methods, such as traditional game approaches, group activities, and habit-based learning, have proven effective in integrating educational character. However, this research also identifies challenges such as lack of teacher training and limited resources as the main obstacles to implementing education with optimal characteristics. The conclusions of this research underline the importance of policy support and ongoing training for teachers to implement character education effectively in physical education learning. Further research is recommended to explore the application of character education in broader and more diverse contexts. Kata Kunci: character education, physical education